Bacterias fitopatogenas identificadas en nogal en España - Lopez, M.M.=700 1 Marti, R.; Morente, C.; Orellana, N.; Ninot, T.; Aleta, N.
(Es, En)
ilus., 12 ref.
Keywords: BACTERIA; JUGLANS REGIA; AGROBACTERIUM TUMEFACIENS; XANTHOMONAS CAMPESTRIS; ERWINIA; ESPAÑA; NOGAL; ERWINIA NIGRIFLUENS